Optimasi lama fermentasi biji kakao (Theobroma cacao L.) terhadap kualitas coklat batang - Oessoe, Yoakhim Y. E.; Lamaega, Jolanda Ch. E.; Lagombi, Christin L.; Umboh, Riel J. J. (Pro Food, 2025)
Fermentation is a critical stage in post-harvest processing of cocoa beans that affects the formation of precursors of the aroma and distinctive taste of chocolate. Fermentation of cocoa beans that is too fast causes the color of the cocoa to still be purple, does not have a distinctive aroma and is dominated by bitter and sour taste, while too long causes rancidity and an astringent aroma. This study aims to identify the best fermentation time to produce chocolate bars that are preferred by consumers, by analyzing the effect of variations in fermentation time on sensory characteristics (color, aroma, taste, and texture) and fat content of chocolate bars. This study used a Completely Randomized Design (CRD) with four fermentation time treatments (4,5,6, and 7 days), three replications, and post-hoc analysis of the Least Significant Difference (LSD). The results of this study indicate that the fermentation time can increase fat content with values ranging from 42.33% (A1) to 58.66% (A4). Sensory evaluation conducted by preference test showed a preference level of “rather like” to “like” in all treatments, with an average color ranging from 5.46-5.70, aroma ranging from 5.13-5.70, taste ranging from 4.50-5.73, and texture ranging from 5.40-5.56. Specifically, extended fermentation time can reduce the bitter taste, resulting in a more preferred chocolate bar. This study concluded that a fermentation time of 6 days is the optimal fermentation time to produce chocolate bars with high fat content and the most preferred color, aroma, taste, and texture characteristics.